Micro-influencers y publicidad. Transparencia y ética en la creación de contenido - Fernández Gómez, Erika; Quintas Froufe, Natalia (Doxa comunicación, 2025)
Atendiendo al auge de la profesión de influencer en la que se crean contenidos comerciales para marcas y ante el debate sobre cuya colaboración no es identificada ante los públicos, se abordan desde la perspectiva de este colectivo sus inquietudes en cuanto a transparencia y ética de su actividad. Para ello se ha preguntado a 290 micro-influencers, influencers de menos de 100.000 seguidores que sin dedicarse profesionalmente a esta actividad, registran mayor nivel de engagement. Según este prescriptor digital, los seguidores conocen las marcas con las que trabajan, son conscientes de que les obsequian con sus productos y aceptan los contenidos comerciales. Sin embargo, para identificar las colaboraciones recurren en mayor medida a fórmulas más ambiguas como mencionar a la marca frente a incorporar una etiqueta identificativa de publicidad, método recogido en las principales normativas. Denuncian asimismo prácticas poco éticas por parte de la industria ante la falta de monetización de su actividad, así como la ausencia de formación en materia de transparencia.
Micro-influencers and advertising. Transparency and ethics in content creation
Due to the emergence of the influencer as a profession in which commercial content is created to the benefit of brands, and faced with the controversy of not always disclosing this collaboration to the public, the concern regarding the transparency and ethics of influencer activity has been addressed in this paper from the viewpoint of these prescribers. For this purpose, 290 micro-influencers, who are those with less than 100,000 followers, were surveyed. Their selection was based on the fact that despite not working exclusively in this profession, they have a higher level of engagement than influencer groups. According to these prescribers, their followers know the brands they work with, and their fans are aware that they are given these products as gifts free of charge. As such, they accept the advertising content offered. However, the influencers do not always divulge this commercial partnership openly, but rather clandestinely, such as by mentioning the brand rather than using a clear advertising label, the latter of which is a practice that is included in standard regulations. The influencers also complain of unethical practices by companies due to the lack of monetization of their activity, as well as the lack of training in transparency.
Keywords: micro-influencers; publicidad; contenido digital; transparencia; ética; advertising; digital content; transparency; ethics